Idiopathic interstitial pneumonias other than idiopathic pulmonary fibrosis - Maher,TM (2017)
The idiopathic interstitial pneumonias (IIPs) represent a group of diffuse parenchymal lung diseases comprising a number of distinct clinic-pathological entities. The most common of the IIPs, idiopathic pulmonary fibrosis (IPF) is dealt with elsewhere in this book. The remaining entities were first formally classified in an American Thoracic Society and European Respiratory Society joint guideline published in 2002 with a further update published in 2013 (1, 2). The genesis for the 2002 guidelines was the observation that distinct histopathologic forms of idiopathic interstitial lung disease manifest distinct clinical syndromes with differences in radiologic appearances and, importantly, prognosis. The 2013 update reflected improved understanding of the IIPs gained following publication of the 2002 document. The key changes were the separation of IIPs into groups of major and rare disorders with further sub-division of the major group into chronic fibrosing, smoking-related and acute/subacute IIPs. With this in mind, this chapter provides an overview of the currently accepted IIP diagnostic entities with a focus on clinical presentation, diagnosis, clinical course and treatment (with the caveat that there are no approved or evidence-based treatments for this disparate group of disorders).